DESKRIPSI MORFOLOGIS NEMATODA SALURAN PENCERNAAN KAMBING KACANG (Capra hircus aegagrus) DI KOTA KUPANG-NUSA TENGGARA TIMUR - Frans Umbu Datta; Theresia Tinenti; Annytha Ina Rohi Detha; Nancy D. F. K. Foeh; Nemay A. Ndaong (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
Local Goats (Capra hircus aegagrus) is a type of small ruminants and is a home-grown in Indonesia which is very susceptible to attack by diseases caused by gastrointestinal parasites, especially in developing countries, causing losses to infected animals and economic losses to farmers. This study aims to know the morphology and total of eggs and adult worms, in the digestive tract in Kupang City- East Nusa Tenggara. This study uses work methods including total calculation and identification of worm eggs using the McMaster method, aiming to calculate the number of worm eggs and used to identify the morphology of worm eggs, total testing and morphology of adult worms in the digestive tract aims to determine the number of adult worms in the digestive tract, Semichenetic Acetic Camine staining aims to confirm and clarify the type from the results of identification of adult worms found in goat intestines after it is determined the dominant type of adult worms in the digestive tract of local goats. The results showed that there were three types of worm eggs found from 20 local goats, namely Trichuris sp as many as 5, Strongyloides sp as many as 63, and Strongyloid sp as many as 304 and there were three categories of infection, namely infection-free category in two goats (TTGT = 0), mild infections in three goats (TTGT = 300-400 or ranged from 1-499), and moderate infections in 15 goats (TTGT = 500-2850 or ranged from 500-> 5000). The results of the total study of adult worms in the digestive tract from four local goats found one type of digestive tract worms, namely Trichuris sp as many as 120 of the two goats (numbers 2 and 4). Trichuris sp as the most dominant type of worm in the digestive tract of local goats in Kupang City, East Nusa Tenggara.